Controlling shareholder, expropriations and firm's leverage decision: Evidence from Chinese Non-tradable share reform - Liu, Qigui; Tian, Gary (Journal of Corporate Finance, 2012)
This paper examines the effect of excess control rights on the leverage decisions made by Chinese non-SOEs before and after the Non-tradable share reform (NTS reform). We find that firms with excess control rights have more excess leverage and their controlling shareholders use the resources for tunneling rather than investing in positive NPV projects. We also find that excess leverage in firms with excess control rights decreases and the market reaction to announcements of related party transactions are more positive after NTS reform. This confirms that tunneling by the controlling shareholders actually reduced. We argue that in emerging markets where legal protection for creditors and shareholders is weak, controlling shareholders borrow excess debt to tunnel through inter-corporate loans and related party transactions. Furthermore the privatization of these economies can reduce the controlling shareholders' tunneling activities and associated excess leverage which destroys firm value.